The Embodied needs of Women in the Workplace: An Exploratory study - Chimhandamba, Nyasha Aura (Graduate School of Business (GSB), 2022)
Women and men face differences in how they experience the work environment concerning health and safety and their needs within the workspace. Depending on age, ethnicity, and socioeconomic status, women and men face different stigmas, thus impacting their difficulties within their work environments. Owing to this knowledge, the purpose of this research was to explore this difference in the workplace and understand how women experience the workplace differently. Specifically, from a perspective of embodiment and the needs, women are often inclined to have as a result of biology in the workplace. This insightful study explored the personalisation of embodiment by examining the diversified understanding of embodied needs of women that existed within different levels of an organisational hierarchy and had varied roles that required different levels of skills, manual labour, and knowledge. Using qualitative interviews and a phenomenological approach, the realities of these women with different embodied needs, and embodied stages were explored. The central insight being that while women may suffer the same injustices in the workplace and share the same biology, their embodied needs and experience still vary and cannot be painted with the same brush. Through this qualitative insight, key themes such as pregnancy and maternal needs, workplace accommodations, women clinic services and women workplace accommodations were identified as components of the female embodied needs. This exploratory study brought light to this understanding by exploring the varied experience of 12 participants.